Predictive value of maternal serum placental growth factor, maternal clinical features, and fetal ultrasound indicators in preeclampsia - Yuee Ling; Hua Wu; Jing Li; Yanhua Ma; Shanshan Zhang; Yanqun Lu; Juan Feng; Sumei Wang; Xuxia Liang (BMC Pregnancy and Childbirth)
Abstract Objective This study was aimed to evaluate the predictive value of placental growth factor (PLGF), maternal risk factors, and maternal-fetal ultrasound indicators for preeclampsia(PE) and to analyze delivery outcomes associated with PE. Methods Pregnant women with PE(n = 80) and healthy controls(n = 160) were enrolled from the People’s Hospital of Guangxi Zhuang Autonomous Region between 2021 and 2022. Serum PLGF level were measured at various stages of pregnancy: early pregnancy, mid-pregnancy, and late pregnancy. Maternal clinical features, fetal ultrasound indicators, and pregnancy outcomes were also recorded. Results The serum concentration of PLGF was lower in the PE group compared to the control group throughout early, middle, and late pregnancy. At 20–24 weeks, the uterine artery resistance index was higher in the preeclampsia group (P < 0.05). Logistic regression analysis identified PLGF concentrations in early pregnancy and mid-pregnancy, along with mean arterial pressure (MAP), as independent factors for the onset of PE (P < 0.05). Conclusion PLGF could be used for prediction of PE in early pregnancy. A predictive model for PE was established by combining the PLGF concentrations in early and middle pregnancy with MAP.